Capacitive DNA sensor for rapid and sensitive detection of whole genome human herpesvirus‐1 dsDNA in serum. Issue 12 (20th April 2017) - Cheng, Cheng; Oueslati, Rania; Wu, Jayne; Chen, Jiangang; Eda, Shigetoshi
Abstract : This work presents a rapid, highly sensitive, low‐cost, and specific capacitive DNA sensor for detection of whole genome human herpesvirus‐1 DNA. This sensor is capable of direct DNA detection with a response time of 30 s, and it can be used to test standard buffer or serum samples. The sensing approach for DNA detection is based on alternating current (AC) electrokinetics. By applying an inhomogeneous AC electric field on sensor electrodes, positive dielectrophoresis is induced to accelerate DNA hybridization. The same applied AC signal also directly measures the hybridization of target with the probe on the sensor surface. Experiments are conducted to optimize the AC signal, as well as the buffers for probe immobilization and target DNA hybridization. The assay is highly sensitive and specific, with no response to human herpesvirus‐2 DNA at 5 ng/mL and a LOD of 1.0 pg/mL (6.5 copies/μL or 10.7 aM) in standard buffer. When testing the double stranded (ds) DNA spiked in human serum samples, the sensor yields a LOD of 20.0 pg/mL (129.5 copies/μL or 0.21 femtomolar (fM)) in neat serum. In this work, the target is whole genome dsDNA, consequently the test can be performed without the use of enzyme or amplification, which considerably simplifies the sensor operation and is highly suitable for point of care disease diagnosis.